Stellar laboratories: VI. New Mo iv - vii oscillator strengths and the molybdenum abundance in the hot white dwarfs G191-B2B and RE0503-289 - Rauch, Thomas; Demleitner, Markus (Arxiv, 2015)
For the spectral analysis of high-resolution and high-signal-to-noise (S/N) spectra of hot stars, state-of-the-art non-local thermodynamic equilibrium (NLTE) model atmospheres are mandatory. These are strongly dependent on the reliability of the atomic data that is used for their calculation. To identify molybdenum lines in the ultraviolet (UV) spectra of the DA-type white dwarf G191-B2B and the DO-type white dwarf RE0503-289 and to determine their photospheric Mo abundances, newly calculated Mo IV - VII oscillator strengths are used. We identified twelve Mo V and nine Mo VI lines in the UV spectrum of RE0503-289 and measured a photospheric Mo abundance of 1.2 - 3.0 x 10**-4 (mass fraction, 22500 - 56400 times the solar abundance). In addition, from the As V and Sn IV resonance lines, we measured mass fractions of arsenic (0.5 - 1.3 x 10**-5, about 300 - 1200 times solar) and tin (1.3 - 3.2 x 10**-4, about 14300 35200 times solar). For G191-B2B, upper limits were determined for the abundances of Mo (5.3 x 10**-7, 100 times solar) and, in addition, for Kr (1.1 x 10**-6, 10 times solar) and Xe (1.7 x 10**-7, 10 times solar). The arsenic abundance was determined (2.3 - 5.9 x 10**-7, about 21 - 53 times solar). A new, registered German Astrophysical Virtual Observatory (GAVO) service, TOSS, has been constructed to provide weighted oscillator strengths and transition probabilities. Reliable measurements and calculations of atomic data are a prerequisite for stellar-atmosphere modeling. Observed Mo V - VI line profiles in the UV spectrum of the white dwarf RE0503-289 were well reproduced with our newly calculated oscillator strengths. For the first time, this allowed to determine the photospheric Mo abundance in a white dwarf.
Gesehen am 08.11.2017